Non-enzymatic electrochemical detection of glucose using Ni–Cu bimetallic alloy nanoparticles loaded on reduced graphene oxide through a one-step synthesis strategy. Issue 46 (15th November 2021) - Xu, Xiaoyun; Tan, Rong; Lv, Xiaoyi; Geng, Chao; Li, Yanping; Cui, Bo; Fang, Yishan
Abstract : Non-enzymatic electrochemical detection of glucose using Ni–Cu bimetallic alloy nanoparticles loaded on reduced graphene oxide through a one step synthesis strategy. Abstract : In this work, Ni–Cu bimetallic alloy nanoparticles supported on reduced graphene oxide (Ni–Cu ANPs/RGO) was successfully fabricated through a one-step hydrothermal synthesis method, where simultaneous reduction of graphene oxide, nickel salt and copper salt was performed, and relevant characterization studies were executed. This synthetic method does not require surfactants and high temperature treatment, and is recommended as a green, convenient and effective way to produce composites. The unique two-dimensional architecture of the RGO provides a large specific surface area, contributing to loading more Ni–Cu ANPs, while the uniformly distributed Ni–Cu bimetallic alloy nanoparticles enhance the electrocatalytic performance of glucose oxidation. The non-enzymatic glucose biosensor based on Ni–Cu ANPs/RGO showed a wide linear range (from 0.01 μM to 30 μM), low detection limit (0.005 μM), and excellent sensitivity (1754.72 μA mM −1 cm −2 ). More importantly, the high reliability and the excellent selectivity in actual sample detection will broaden its practical application in electrochemical sensing.